Influence of cardiorespiratory fitness and body composition on resting and post-exercise indices of vascular health in young adults - Rian Q. Landers-Ramos; Kathleen Dondero; Ian Imery; Nicholas Reveille; Hannah A. Zabriskie; Devon A. Dobrosielski (Sports Medicine and Health Science, 2024)
Poor cardiorespiratory fitness may mediate vascular impairments at rest and following an acute bout of exercise in young healthy individuals. This study aimed to compare flow mediated dilation (FMD) and vascular augmentation index (AIx75) between young adults with low, moderate, and high levels of cardiorespiratory fitness before and after an acute bout of aerobic exercise. Forty-three participants (22 men; 21 women) between 18 and 29 years of age completed the study. Participants were classified into low, moderate, and high health-related cardiorespiratory fitness groups according to age- and sex-based relative maximal oxygen consumption (V˙O2 max) percentile rankings. FMD was performed using Doppler ultrasound and AIx75 was performed using pulse wave analysis at baseline and 60-min after a 30-min bout of treadmill running at 70% V˙O2 max. A significant interaction (p ​= ​0.047; ηp2 ​= ​0.142) was observed, with the moderate fitness group exhibiting a higher FMD post-exercise compared with baseline ([6.7% ​± ​3.1%] vs. [8.5% ​± ​2.8%], p ​= ​0.028; d ​= ​0.598). We found a significant main effect of group for AIx75 (p ​= ​0.023; ηp2 ​= ​0.168), with the high fitness group exhibiting lower AIx75 compared to low fitness group ([−10% ​± ​10%] vs. [2% ​± ​10%], respectively, p ​= ​0.019; g ​= ​1.07). This was eliminated after covarying for body fat percentage (p ​= ​0.489). Our findings suggest that resting FMD and AIx75 responses are not significantly influenced by cardiorespiratory fitness, but FMD recovery responses to exercise may be enhanced in individuals with moderate cardiorespiratory fitness levels.